Morphological and ultrastructural effects of microcystin-LR from Microcystis aeruginosa extract on a kidney cell line - Alverca, E. (2015)
The aim of this study was to examine the toxic effects of a microcystin-LR (MCLR)-containing cyanobacteria extract on the subcellular organization of a kidney cell line (Vero-E6). Cells were exposed to different MCLR concentrations (1.3-150 mu M) for 24, 48 and 72 h and two cytotoxicity assays were performed. This information was combined with the analysis of lysosomal, mitochondrial and cytoskeleton integrity and with an ultrastructural study. Biochemical and microscopic data revealed a good agreement and demonstrated that cellular response to MCLR is dependent on the dose/exposure time. Cell viability decayed markedly after 24 h of exposure to toxin concentrations greater than 30 PM. Furthermore, it was demonstrated that lysosome destabilization precedes mitochondria dysfunction. The ultrastructural analysis showed that mild toxin incubation conditions induce endoplasmic reticulum (ER) vacuolization and assembly of large autophagic vacuoles, suggesting that autophagy is an early cellular response to the toxin. After exposure to higher MCLR doses, the number of apoptotic cells increased, as identified by microscopic observations and confirmed with TUNEL assay. Additionally, drastic exposure conditions induced the increase of necrotic cells. These results suggest that the ER is the primary microcystin target in Vero cells and that autophagy, apoptosis and necrosis are induced in a dose- and time-dependent manner. (C) 2009 Elsevier Ltd. All rights reserved.. - Portuguese Foundation for Science and Technology [SFRH/BD/10585/2002]; National Health Institute, Portugal. - To Portuguese Foundation for Science and Technology for grant SFRH/BD/10585/2002 attributed to Elsa Dias. To National Health Institute, Portugal, for a master fellowship attributed to Mariana Andrade. To Institute for Medicine and Pharmaceutical Sciences (I-Med) and to Centre for Research on Human Molecular Genetics (CIGMH).